The Influence of Indonesian Cardio Gymnastic Series-I to Plasma Protein Expression Of BDNF in The Elderly - Nita Fitria; Lynna Lidyana; Shelly Iskandar; Leonardo Lubis; Fidella Fidella; Ajeng Fitria; Ambrosius Purba (NurseLine Journal, 2019)
Physical activity in the elderly will improve cognitive function. Biomolecular changes to see an increase in elderly cognitive function are characterized by an increase in the expression of plasma protein Brain Derived Nerve Factor (BDNF). Efforts to improve cognitive function can be done in Indonesian Cardio Gymnastic Serie-I . In this study the aim was to analyze the influence of Indonesian Cardio Gymnastic Serie-I three times a week for 6 weeks to Plasma Protein Expression of BDNF in Elderly. This study used a pre-experiment with the design of one group pre and post test for 27 samples of healthy elderly aged > 60 years and routinely conduct Indonesian Cardio Gymnastic Serie-I 3 times a week for 6 weeks. To determine BDNF levels taken from elderly plasma blood then measured using the Enzime Link Immunosorbent Assay (ELISA) method. To analyze the influence of Indonesian Cardio Gymnastic Serie-I to plasma protein expression of BDNF, a paired t-test was used so that the mean differences between before and after gymnastics were known. There were differences in the mean BDNF plasma protein expression before and after Indonesian Cardio Gymnastic Serie-I (2174,52 ± 700,79 VS 1981 ± 915,17 pg/ mL, p = 0,40 ; p > 0,05) with the mean difference was 192,69 which means Indonesian Cardio Gymnastic Serie-I 3 times a week for 6 weeks had no influence to plasma protein expression of BDNF because the level has decreased by 91.14% after exercising